1997
DOI: 10.1084/jem.186.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Development of Eosinophilic Airway Inflammation and Airway Hyperresponsiveness in Mast Cell–deficient Mice

Abstract: Mast cells are the main effector cells of immediate hypersensitivity and anaphylaxis. Their role in the development of allergen-induced airway hyperresponsiveness (AHR) is controversial and based on indirect evidence. To address these issues, mast cell–deficient mice (W/W  v) and their congenic littermates were sensitized to ovalbumin (OVA) by intraperitoneal injection and subsequently challenged with OVA via the airways. Comparison of OVA-specific immunoglobulin E (IgE) levels in the serum and numbers of eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
297
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 381 publications
(323 citation statements)
references
References 29 publications
20
297
6
Order By: Relevance
“…Indeed, there are studies supporting the role of mast cells in these models (10,11). However, there are other reports in the literature that question mast cell participation in this response (12)(13)(14)(15). Recently, strong evidence has been presented that ties the role of mast cells in murine models of asthma to the experimental protocols used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, there are studies supporting the role of mast cells in these models (10,11). However, there are other reports in the literature that question mast cell participation in this response (12)(13)(14)(15). Recently, strong evidence has been presented that ties the role of mast cells in murine models of asthma to the experimental protocols used.…”
Section: Discussionmentioning
confidence: 98%
“…While some reports have demonstrated that mast cell deficiency results in attenuated eosinophilic airway inflammation (10,11), others have shown that this deficiency does not affect allergic airway inflammation and AHR (12)(13)(14)(15). Recent studies have suggested that the extent to which mast cells contribute to airway inflammation and AHR in mice is highly dependent on the experimental model used to generate the airway response (16,17).…”
mentioning
confidence: 99%
“…While some reports have demonstrated that mast cell activation results in a potentiation of late AHR [8][9][10], others have shown that AHR can be elicited in the absence of IgE Ab [17,18] or mast cells [19], dependent on the experimental model used to generate the airway response. These data have come from studies that used a protocol that consists of airway antigen challenge for more than 3 consecutive days, and examination of AHR usually 2 days after the last antigen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…AHR was also assessed as a change in airway function after challenge with aerosolized methacholine via airways, as described elsewhere [39,40]. Anesthesia was achieved with 80 mg/kg of pentobarbital sodium injected i.p.…”
Section: Determination Of Ahrmentioning
confidence: 99%
“…There are quite a lot of evidential data demonstrating a pivotal role for IgE in the development of bronchial asthma: increased IgE serum levels are associated with prevalence rates and disease severity (31,32), asthma in children is almost always associated with production of allergen-specific IgE and positive skin test reactivity against environmental allergens (8,31), and even in patients with non-allergic asthma, despite normal IgE serum levels, an extensive production of IgE in large areas of the airways has been found (36). On the other hand, experimental data from murine models demonstrate that development of airway inflammation and hyperreactivity to unspecific stimuli, two of the three main features of the disease, may occur independently of B cells (78), IgE-production (78,79) or IgE-mediated mast-cell activation (80). Concordantly, in animals with a robust allergen-mediated inflammatory response of the airways, treatment with anti-IgE antibodies does not inhibit development of airway inflammation or hyperreactivity (81).…”
Section: Discussionmentioning
confidence: 99%